Implikasi nama Allah Al-Ahad terhadap kurikulum pendidikan karakter - Taufik, Buldan (Tawazun: Jurnal Pendidikan Islam, 2022)
Islam pays great attention to The Character Of Education. The superiority of the friendships to have the qualified knowledge and become a reference for menkind until the end of time, and it cannot be separated from the way of the Prophet ï² who prioritized their character education before devoting all knowledge, and this character education continues to be instilled together with knowledge. The Moral of education or character today is not less popular even in Western education, but The conditions in the field of moral decline are anywhere. There needs to be a conceptual solution to the implementation way of the character of education should be. The Divining guidance through Asmaul Husna is full of character education, not a few people perform it regularly, but unfortunately it has not reached the ta’abbud according to what the Shari’ah wants, which is not only memorizing or creating, but also understanding and practicing its contents. In educational institutions, it is necessary to formulate the right way to imply the character of education on the basis of Allah’s revelation through the right curriculum. This study uses a qualitative method with a library research model, in which the researcher is the main instrument. The author chose one of the Asmaul Husna as the object of study, namely the name Allah "Al-Ahad", and it is found that from this one great name has a strong implication on the character of education curriculum both on objectives’ content, methods, and evaluation. Abstrak Islam sangat memperhatikan pendidikan karakter. Keunggulan para sahabat hingga memiliki ilmu yang mumpuni dan menjadi rujukan ummat manusia hingga akhir zaman, tidak terlepas dari cara Nabi r yang mengutamakan pendidikan karakter mereka sebelum mencurahkan segala ilmu, dan pendidikan karakter ini terus ditanamkan berbarengan dengan ilmu. Pendidikan akhlak atau karakter dewasa ini tidak kalah bergembar-gembor hingga dalam pendidikan Barat sekalipun, namun kondisi di lapangan kemerosotan akhlak terjadi di mana-mana. Perlu ada solusi konseptual bagaimana semestinya pelaksanaan pendidikan karakter. Petunjuk ilahi melalui asmaul husna sarat akan pendidikan karakter, tidak sedikit orang yang mewiridkannya secara rutin, namun sayangnya belum sampai pada ta’abbud sesuai yang diinginkan syariat, yang bukan hanya menghafal atau mewiridkan, tapi juga memahami dan mengamalkan kandungannya. Di lembaga pendidikan, perlu formulasi yang tepat bagaimana pelaksanaan pendidikan karakter dengan basis wahyu Allah ini melalui kurikulum yang tepat. Penelitian ini menggunakan metode kualitatif dengan model studi kepustakaan (library research), di mana peneliti sebagai instrumen utamanya. Penulis memilih salah satu asmaul husna sebagai objek kajian, yaitu nama Allah "Al-Ahad”, dan didapati dari satu nama yang Agung ini implikasi yang kuat pada kurikulum pendidikan karakter baik pada tujuan, isi, metode, maupun evaluasi.